Building up the eco-system of innovative entrepreneurship: theoretical and practical stands of view - Trang, Nguyen Ha Quynh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
The building of the innovative startup ecosystem and the offering of favorable conditions for its sustainable development have become the topics of deep concerns by the Government and the academic community during recent years. The topics get particularly attractive in the context of Industrial Revolution 4.0 (IR 4.0) which offers new opportunities and challenges to all nations. The systematization of basic notions and concepts would help researchers and policy makers have a clearer view on the necessity to build the innovative startup ecosystem. After providing the basic notions and a brief interpretation of the specific features of the innovative startup ecosystem, the author presents experiences learnt from other nations in building the innovative startup ecosystem as well as some suggestions for this work in Vietnam which are presented in form of questions for research. Code: 19010901